Accident Prevention on the Basis of Accidental Analysis during Curved Road - TACHIWANA, Shin'ichi; DOI, Shota; DOI, Shun'ichi; WAKABAYASHI, Hiroshi (TRANSACTIONS OF THE JAPAN SOCIETY OF MECHANICAL ENGINEERS Series C, 2013)
Factors in traffic accident include three elements “road traffic environments, vehicle and driver”. Therefore, it is important to analyze the accident on the basis of combination of those three elements. However, the conventional road safety measures have been carried out on the basis of the independently element. In this paper, we make clear the risk of accident that occurred by acting those three elements synergistically. In addition, we propose the visual measures, and verify its effect. As a result, the risk of accident taking into consideration the driver's factor in addition to changing conditions of vehicle and environment was clarified. In the verification of measures effect, the gaze point instruction line had measures effect for the vehicle of drift behavior. Moreover, it was suggested that the cat's-eye have effect for subjects that start steering behavior late.